Systematic Literature Review: Kemampuan Berpikir Kritis Matematis Siswa Ditinjau dari Adversity Quotient - Irfiani, Virga; Junaedi, Iwan; Waluya, Stevanus Budi (Indonesian Journal Publisher, 2024)
Critical thinking skills are very important in 21st century mathematics learning. Critical thinking skills need to exist in every student in order to solve various kinds of problems, especially mathematical problems. According to Facione (2013) the indicators of critical thinking skills are: (1) interpretation, (2) analysis, (3) evaluation, (4) inference, (5) explanation, and (6) self-regulation. A student's response when encountering an obstacle is known as adversity quotient. Adversity quotient has three different types of levels namely: (1) climber, (2) camper, and (3) quitter. The purpose of the following research is to describe the type of research used, research trends related to students' mathematical critical thinking skills in terms of adversity quotient from 2018-2023, and the effect of adversity quotient on students' mathematical critical thinking skills. SLR is the method used by this research. The data collection technique was carried out by reviewing articles related to students' mathematical critical thinking skills in terms of adversity quotient in articles published around 2018-2023. There were 10 articles found through google schoolar and scopus. The results of this study show: (1) the type of research that is often used is qualitative; (2) most research is conducted at the junior high school level; (3) adversity quotient has a positive influence on the results of students' mathematical critical thinking skills.